2020
DOI: 10.1007/s00226-020-01192-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fractionally distilled Picea abies TMP-turpentine on wood-decaying fungi: in vitro, microcosm and field experiments

Abstract: Synthetic and heavy metal antifungals are frequently used as wood preservatives. However, they exhibit relatively inert biodegradation and toxic properties when leached; this makes their replacement with environmentally degradable yet functional alternatives a key target in the wood protection industry. In this context, distilled fractions of raw thermomechanical pulp turpentine (TMP-T) from Picea abies were assessed for their wood protecting capabilities against wood-decaying fungi. Antifungal bioactivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…betulina . In addition, Ljunggren et al found that himachalene showed effective antifungal activity against C. puteana.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…betulina . In addition, Ljunggren et al found that himachalene showed effective antifungal activity against C. puteana.…”
Section: Resultsmentioning
confidence: 99%
“…Another study indicated that the antifungal effect of sesquiterpenes against the brown-decay fungus L. sulphureus was high compared to that of the white-decay fungus L. betulina . 16 In addition, Ljunggren et al 64 found that himachalene showed effective antifungal activity against C. puteana .…”
Section: Resultsmentioning
confidence: 99%
“…Another study indicated that the antifungal effect of sesquiterpenes against the brown-decay fungus L. sulphureus was high compared to that of the white-decay fungus L. betulina (Wu et al 2022). In addition, Ljunggren et al (2020) found that himachalene showed effective antifungal activity against C. puteana.…”
Section: Establishment Of Response Prediction Modelsmentioning
confidence: 99%